2007
DOI: 10.1021/bi7003203
|View full text |Cite
|
Sign up to set email alerts
|

LCAT can Rescue the Abnormal Phenotype Produced by the Natural ApoA-I Mutations (Leu141Arg)Pisa and (Leu159Arg)FIN

Abstract: To explain the etiology and find a mode of therapy of genetically determined low levels of high-density lipoprotein (HDL), we have generated recombinant adenoviruses expressing apolipoprotein A-I (apoA-I)(Leu141Arg)Pisa and apoA-I(Leu159Arg)FIN and studied their properties in vitro and in vivo. Both mutants were secreted efficiently from cells but had diminished capacity to activate lecithin/cholesterol acyltransferase (LCAT) in vitro. Adenovirus-mediated gene transfer of either of the two mutants in apoA-I-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 36 publications
5
62
1
Order By: Relevance
“…Interestingly, plasma cholesterol esterifi cation fl uxes did not differ between cases and controls, indicating cholesterol esterifi cation independent of plasma apoA-I levels. In line , LCAT gene therapy has been demonstrated to correct low HDL-c levels in mice with mutations in APOA1 ( 38 ). Previous studies in humans have also suggested that plasma CE clearance is mostly mediated by apoB100-containing particles following CETP-mediated transfer, rather than by direct HDL-dependent CE removal ( 13,39,40 ).…”
Section: Statistical Analysesmentioning
confidence: 97%
“…Interestingly, plasma cholesterol esterifi cation fl uxes did not differ between cases and controls, indicating cholesterol esterifi cation independent of plasma apoA-I levels. In line , LCAT gene therapy has been demonstrated to correct low HDL-c levels in mice with mutations in APOA1 ( 38 ). Previous studies in humans have also suggested that plasma CE clearance is mostly mediated by apoB100-containing particles following CETP-mediated transfer, rather than by direct HDL-dependent CE removal ( 13,39,40 ).…”
Section: Statistical Analysesmentioning
confidence: 97%
“…The apoA-I gene lacking the BglII restriction site, which is present at nucleotide position 181 of the genomic sequence relative to the ATG codon of the gene, was cloned into the pCD-NA3.1 vector to generate the pCDNA3.1-apoA-I( ⌬ BglII) plasmid as described ( 11 ). This plasmid was used as a template to introduce the apoA-I mutations F225A/V227A/F229A/L230A using the QuickChange® XL mutagenesis kit (Stratagene, Santa Clara, CA) and the mutagenic primers shown in supplementary Table I.…”
Section: Generation Of Adenoviruses Expressing the Wild-type And Mutamentioning
confidence: 99%
“…Recombinant adenoviruses expressing the WT and the mutant apoA-I were constructed using the Ad-Easy-1 system in which the recombinant adenovirus construct is generated in bacteria BJ-5183 (purchased from Stratagene) ( 12 ). The recombinant adenovirus was packaged in 911 cells, amplifi ed in human embryonic kidney 293 (HEK 293) cells, purifi ed, and titrated as described ( 11 ).…”
Section: Generation Of Adenoviruses Expressing the Wild-type And Mutamentioning
confidence: 99%
See 2 more Smart Citations